2020
DOI: 10.1128/aac.02375-19
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of KBP-7072, a Novel Third-Generation Tetracycline, against 531 Recent Geographically Diverse and Molecularly Characterized Acinetobacter baumannii Species Complex Isolates

Abstract: KBP-7072 is a novel third-generation tetracycline (aminomethylcycline) antibacterial that overcomes common efflux and ribosomal protection resistance mechanisms that cause resistance in older-generation tetracyclines. KBP-7072 completed phase 1 clinical development studies for safety, tolerability, and pharmacokinetics (ClinicalTrials.gov identifier NCT02454361) and multiple ascending doses in healthy subjects (ClinicalTrials.gov identifier NCT02654626) in December 2015. Both oral and intravenous formulations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
1
11
2
Order By: Relevance
“…[19][20][21] on values <1 mcg/mL across a range of pathogens, including typical and atypical pathogens associated with CABP. [22][23][24] In a murine mouse model of pneumonia, peak KBP-7072 concentrations ranged from 0.12 to 25.2 mcg/mL. 17 Thus, the doses used in this study were severalfold greater than previously reported to produce static and cidal effects.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] on values <1 mcg/mL across a range of pathogens, including typical and atypical pathogens associated with CABP. [22][23][24] In a murine mouse model of pneumonia, peak KBP-7072 concentrations ranged from 0.12 to 25.2 mcg/mL. 17 Thus, the doses used in this study were severalfold greater than previously reported to produce static and cidal effects.…”
Section: Discussionmentioning
confidence: 99%
“…The mean f AUC/MIC ratio required for achieving a bacteriostatic effect of KBP-7072 was 4.39 and for achieving 1-log 10 kill and 2-log 10 kill was 8.34 and 13.46, respectively. Previous in vitro studies with KBP-7072 demonstrated MIC 90 values <1 μg/mL across a range of Gram-negative and Gram-positive pathogens, including multidrug resistant and typical and atypical pathogens associated with CABP (Huband et al, 2020). 15…”
Section: Discussionmentioning
confidence: 97%
“…Aminoglycosides in combination with other antibiotics are usually prescribed for treating meningitis or bacteremia and have shown promising activity against A. baumannii in in vivo and in vitro studies [ 119 , 137 ]. Tetracycline is also preferred to treat A. baumannii infections in several experimental and clinical studies [ 138 ].…”
Section: Antimicrobial Therapymentioning
confidence: 99%